2008
DOI: 10.1063/1.2903508
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between microstructure, electronic properties and flicker noise in organic thin film transistors

Abstract: We report on observations of a correlation between the microstructure of organic thin films and their electronic properties when incorporated in field-effect transistors. We present a simple method to induce enhanced grain growth in solution-processed thin film transistors by chemical modification of the source-drain contacts. This leads to improved device performance and gives a unique thin film microstructure for fundamental studies concerning the effect of structural order on the charge transport. We demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 9 publications
5
69
1
Order By: Relevance
“…It is well known that metallic films are typically "noisy", exhibiting anomalous colored noise with power law exponent α in the power spectrum describing fluctuations in various properties (particle mobility, potential energy, etc.) that is dependent on T. This noise is arguably a fundamentally limiting factor in diverse manufacturing applications involving the development of electrical devices 61 and sensors, 62 and this type of thermal noise is often found as a complication to high resolution measurement and sensing processes. While it has long been appreciated that this ubiquitous "1/ f " noise is an equilibrium, or near equilibrium, phenomenon in many condensed materials having an origin in mobility fluctuations, a general explanation of this phenomenon has remained elusive.…”
Section: Fig 4 Vanmentioning
confidence: 99%
“…It is well known that metallic films are typically "noisy", exhibiting anomalous colored noise with power law exponent α in the power spectrum describing fluctuations in various properties (particle mobility, potential energy, etc.) that is dependent on T. This noise is arguably a fundamentally limiting factor in diverse manufacturing applications involving the development of electrical devices 61 and sensors, 62 and this type of thermal noise is often found as a complication to high resolution measurement and sensing processes. While it has long been appreciated that this ubiquitous "1/ f " noise is an equilibrium, or near equilibrium, phenomenon in many condensed materials having an origin in mobility fluctuations, a general explanation of this phenomenon has remained elusive.…”
Section: Fig 4 Vanmentioning
confidence: 99%
“…The material studied here, difluoro bis(triethylsilylethynyl) anthradithiophene (diF-TESADT), is one of a number of "designer" organic materials being studied for potential use in organic based electronics. 9 Charge mobilities on the order of 0.4 cm 2 /V•s have been achieved for diF-TESADT spun-cast devices, 10 w hile charge mobilities of 6 cm 2 /V•s have been achieved for single crystal (SC) diF-TESADT OTFTs. 11 Previous studies of spun-cast OTFTs using other organic materials have reported stress effects such as a decrease in drain current and a shift in the threshold voltage (V T ) when the organic material is under an applied gate bias over a period of several hours and these bias stress effects in the linear vs. saturation regimes have been compared.…”
mentioning
confidence: 99%
“…The band-like carrier transport in the present single crystal form of C 8 -DNBDT-NW was unambiguously verified by the Hall effect measurements and electron spin resonance spectroscopy 33,34 . Previous studies about the 1/f noise in disordered organic semiconductors have revealed that the 1/f noise in I D originates mainly from carrier number fluctuation (δn), i.e., δI ∝ e(δn)μ [23][24][25][26] , which is referred to as McWhorter's model (see "Methods" section) 35,36 . McWhorter's model, which is widely adapted to the 1/f noise in inorganic semiconductors, accounts for carrier capture/emission processes at the transistor's gate dielectric interface and describes the resulting current fluctuations.…”
Section: Resultsmentioning
confidence: 99%
“…It has been known that the low-frequency electronic noise commonly observed in OFETs is considered to be flicker noise (1/f noise). Among various models of 1/f noise, the most common manifestation is the McWhorter's model [23][24][25][26] , that is also used to interpret 1/f noise in conventional Si metal-oxidesemiconductor (MOS) FETs 35 . McWhorter's model takes the carrier capture/ emission to the channel into account; the fluctuation of the number of carrier δn leads to current fluctuation, δI ∝ e(δn)μ.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation